Correlative FIB-SEM and TEM investigation of the magnesium electrode - Sankowsi, Andrzej (2025)
The lithium-ion battery (LIB) has been at the forefront of innovations in energy storage since its commercialisation over 30 years ago. As we reach the practical specific capacity limit of current state-of-the-art materials, novel and innovative battery technologies are required to satiate the requirements of energy intensive applications such as electric vehicles. A lithium metal negative electrode has been proposed to increase the energy density. However, the high reactivity causes poor cycling performance due to electrolyte degradation, dendrite formation and safety issues. The magnesium electrode offers a solution that has double the theoretical volumetric capacity of the lithium electrode while simultaneously mitigating dendritic growth, reducing raw material costs and greatly increasing sustainability. Previous work has shown that traditional LIB electrolytes are not compatible with magnesium metal, and the plating and stripping mechanism that underpins how magnesium electrodes cycle is poorly understood.